Synthesis and in vitro antibacterial activity of Cephradine Benzoate (Bangladesh Journal of Medical Science, 2011)
Aims & Methods: The present study was undertaken to compare the antibacterial activity of a cephradine derivative with that of the parent antibiotic cephradine. Cephradine was converted to its benzoyl derivative by Schotten-Baumann method for the first time. Disc diffusion method was employed to find out the antibacterial activity against EPEC, ETEC, E. Agg, Salmonella typhi, Salmonella group B, Shigella boydii, Shigella dysenteriae 1, Shigella dysenteriae 2, Shigella flexinariae and Shigella sonnei. Melting point, TLC, HPLC, UV, FTIR and 1H NMR studies were carried out to check the purity and confirm that the derivative was cephradine benzoate. Results: The benzoyl derivative showed promising activity against tested bacteria. The results obtained from the study demonstrate that the benzoyl derivative could be a potential antibacterial agent. Key words: Cephradine benzoate, antibacterial activity, disc diffusion method.   DOI: http://dx.doi.org/ 10.3329/bjms.v10i3.8356 BJMS 2011; 10(3): 148-151